Multiplication of semi-hard blueberry minicuttings using different substrates (Research, Society and Development, 2021)
The increasing search of the population, in recent years, for healthier products, made this study viable, regarding the evaluation of the following variables: proportion of rooted cuttings, amount of sprouting, number of roots per cutting, average length of roots, unrooted cuttings with callus and proportion of germinated cuttings. The research was carried out in a greenhouse of the Brazilian Agricultural Research Corporation, located in the municipality of Pelotas, in the state of Rio Grande do Sul. The woody mini cuttings evaluated were blueberry, Vaccinium spp, with two cultivars, Bluecrisp and to O'Neal. In a polystyrene tray, containing 72 cells, with 4 repetitions, the following substrates were used: vermiculite, sand, peat, carbonized rice husk, sawdust and Carolina Soil - substrate for commercial use -, in each of the repetitions twelve minis were used. stakes, totaling 48 mini stakes evaluated. The evaluation was carried out during a period of 90 days, and every 15 days the shoots were evaluated and at the end of this period, the evaluation of their roots was also carried out.